HUBUNGAN PEMERIKSAAN DARAH TEPI , SEROLOGIS DAN KLINIS SEBAGAI FAKTOR RESIKO TERJADINYA SYOK DEMAM BERDARAH DENGUE PADA BAYI DAN ANAK - putra, irawan anasta; Syauqy, ahmad; dewi, hasna (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2017)
Abstract Predicting DHF patients that will continue causing Shock or Recurrent Shock is not easy. Based on several studies it appears that examination of peripheral blood, serology, and clinical features into several factors to predict dengue hemorrhagic shock in infants and children. In Jambi there has never been any research related to it. Therefore it is necessary to do research on